The Spark in You - Pippins, Andrea (New York : Random House Studio, 2024)
A young girl unleashes her inner spark and expresses her creativity and uniqueness during Carnival's lively atmosphere.
New kids book 2024 spring.
Ages 3-7.
Grades K-1.
Keywords: Self-perception -- Fiction; Carnival -- Fiction; Holidays & Celebrations; African Americans; Brazil -- Fiction; Picture books